Dinamika Regulasi Sertifikasi Halal di Indonesia - Devid Frastiawan Amir Sup; Annas Syams Rizal Fahmi; Faridl Noor Hilal; Muhammad Irkham Firdaus (JESI (Jurnal Ekonomi Syariah Indonesia), 2020)
The need for halal products in Indonesia is increasing rapidly, considering that Indonesia is a country that has a large Muslim population. To oversee that each product is halal guaranteed, one of the efforts made by the government is through regulation. In Indonesia, this regulation apparently experienced several changes/renewals. This study aims to describe how the dynamics of halal regulation in Indonesia from time to time. The method used is qualitative-descriptive-literature. The result obtained, that there are changes and renewal of regulations relating to the guarantee of halal products in Indonesia are the right steps (in his time) taken by the government to maintain the existence of halal products circulating in Indonesia to be in accordance with the concept of halal in Islam.